2023
DOI: 10.1002/syn.22270
|View full text |Cite
|
Sign up to set email alerts
|

The increase of Nrf2 m6A modification induced by FTO downregulation promotes hippocampal neuron injury and aggravates the progression of epilepsy in a rat model

Abstract: Epilepsy is a common chronic neurological disorder characterized by widespread neuronal death. The purpose of this study was to investigate the role of nuclear factor erythroid 2‐related factor 2 (Nrf2) m6A methylation in epilepsy. To create epileptic models, the rats were given Lithium chloride and pilocarpine, and isolated primary rat hippocampal neurons were cultured in an Mg2+‐free medium. The frequency of seizures was recorded in the epilepsy group of rats. The functional tests included TUNEL, MTT, and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As PTZ challenges only lead to reduced expression of hippocampal YTHDC1, and METTL14 over-expression increased the expression of YTHDC1, so we can conclude YTHDC1 may be the key m6A-binding protein under acute seizures condition. Although previous study showed YTHDF2 was up-regulated in rat epileptic models induced by lithium chloride and pilocarpine [29]. Exactly, YTHDC1 is preferentially expressed in the hippocampus of mouse brains.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As PTZ challenges only lead to reduced expression of hippocampal YTHDC1, and METTL14 over-expression increased the expression of YTHDC1, so we can conclude YTHDC1 may be the key m6A-binding protein under acute seizures condition. Although previous study showed YTHDF2 was up-regulated in rat epileptic models induced by lithium chloride and pilocarpine [29]. Exactly, YTHDC1 is preferentially expressed in the hippocampus of mouse brains.…”
Section: Discussionmentioning
confidence: 73%
“…The N6-methyladenine (m6A) modi cation is one of the most common posttranscriptional RNA modi cations in eukaryotes. Although m6A modi cation is involved in epileptogenesis, such as a recent research veri ed that m6A modi cation play a vital role in hippocampal neuron injury and the progression of epilepsy in a rat model [29]; another study also demonstrated that m6A modi cation was related to immune cell components, cell death patterns and glucose metabolism in the pathogenesis of epilepsy [14]. The results of our tests similarly showed that in acute seizures induced by PTZ injection, the m6A level was signi cantly reduced in the hippocampal of mice, as revealed by m6A-ELISA, m6A-IHC and m6A-dot blot tests, indicating lower m6A level could aggravate the progression of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Upregulation of FTO also suppressed Nrf2 mRNA m6A methylation, leading to enhanced cell viability and reduced apoptosis in rats. 33 …”
Section: Discussionmentioning
confidence: 99%